Modeling the decarburization of expansion droplets based on the solid phase ratio of slag and data fitting during BOF steelmaking process - Zi-cheng Xin; Wen-hui Lin; Jiang-shan Zhang; Kai-xiang Peng; Qing Liu (Scientific Reports)
Abstract In the process of basic oxygen furnace steelmaking, the high-velocity jet impacts the molten metal pool, resulting in the generation of splashing metal droplets with varying particle sizes. The expansion decarburization of metal droplets in the emulsion phase is one of the main steel-slag reaction behaviors. In this paper, firstly, a theoretical decarburization model of expansion droplet was established, finding biases in their calculation results. Then, the solid phase ratio in different FeO content of slag was analyzed, demonstrating its significant impact on the reactivity performance of slag. Finally, an improved decarburization comprehensive model for expanded droplets, based on the solid phase ratio of slag and data fitting, was developed and validated using experimental data. The results indicate that the improved droplet decarburisation comprehensive model shows a good agreement with the experimental data in predicting changes in carbon content, with Pearson correlation coefficient exceeding 0.94 for different FeO contents. ‌For FeO contents of 3%, 10%, 20%, and 30%, the model achieves MAE (0.035%, 0.024%, 0.056%, 0.059%) and RMSE (0.0034%, 0.0019%, 0.011%, 0.018%), respectively. This model can accurately calculate the change of carbon content of metal droplets under various complex multiphase slag conditions.